I trecenteschi statuti del Collegio delle vergini dell’Annunziata di Nola - Tufano, Luigi (FedOA - Federico II University Press, 2026)
The book outlines the history of the Collegio delle vergini dell'Annunziata in Nola. This institution, which was founded in 1393 by the count Nicola Orsini, was intended as a place for the education and the social control of young girls from the local elite. The starting point of this work was the edition of the Statuti de lo Collegio delle vergene de la Annunciata de Nola de lo ordene de Sancta Maria, a particularly valuable source due to the rarity of this type of document in late 14th century Southern Italy. This research pays close attention to social segmentation, to forms of selection and access, and to the management of this institution, which was shared among noble, ecclesiastical and civic powers. Indeed, the Collegio became an instrument of government and territorial construction in a baronial lordship, that was strongly aware of its political function.